Soil health of bananas cultivated in Ribeira River Valley – the major producing region of Brazil - Cavalieri-Polizeli Karina Maria Vieira; da Silva Anderson Lucas; Cremonesi Marcus; Lima Juliana Domingues; Cipriano Patriciani Estela; Cherubin Maurício Roberto; Rozane Danilo Eduardo (Folia Horticulturae)
Soil health receives the increased attention of researchers worldwide to evaluate the sustainability of agricultural land management. Chemical, physical and biological indicators are essential to reflect the soil functioning capacity and its quality. Thus, the aim of this study was to determine the soil health and quality of banana crops compared with natural forests. The experimental area included three counties: Eldorado, Registro and Sete Barras, located in Baixo Vale do Ribeira, in the state of São Paulo, Brazil. In each county, soil from banana orchards was compared with soil collected from the natural Atlantic Forest in the transitional regeneration phase, in split-plot design, considering each county as a block. Soil health was evaluated through six soil quality indexes developed using different strategies to define the minimum dataset, data interpretation (linear or non-linear scoring curves) and integration (additive or weighted). Compared with natural forests, in general, banana crop soil showed elevated values of the chemical indicators, mainly due to the frequent fertiliser applications. A slight decrease, but still adequate, of physical indicators, primarily related to soil aeration and similar results in biological indicators. All soil quality indexes tested here can be used to verify soil health; however, soil quality index-2 was the best for a total dataset, and soil management assessment framework was the best for a minimum dataset, demonstrating no statistical difference in soil health between banana and forest soil systems.